Basic principle for the solution of the building evacuation problem - Salvador Casadesús Pursals; Federico Garriga Garzón (Journal of Industrial Engineering and Management (JIEM), 2009)
Nowadays, there exist different offers to find the solution of the building evacuation problem. As we analyze in the state of the art, this problem can be studied from different perspectives and even as a problem of optimization considering different objectives. We can wonder on which is the most suitable formulation and the response can be as confusing as saying that it depends on our aims. The more important things to study the ideal building evacuation, understood as the distribution of the occupants towards the exits that achieves the minimal evacuation time, are the valid principles for any formulation of the problem. One of them appears in the present work. To expose the principle, we use graphical procedures that are applied to the optimization of the enclosure evacuation. In the exposed procedure, speeds and constant flows of traffic are considered to model the movement of the persons. Ways and possible delays in the beginning of the bulging evacuation are studied
Keywords: 650; Building evacuation; evacuation optimization; optimal building evacuation